Measuring the Reading of Inscriptions on Tombstones in the Past: Theoretical Approach - Tolkačevski, Kšištof (Knygotyra, 2018)
[full article, abstract in English; abstract in Lithuanian]If you own a book, it doesn’t mean at all that you have read it. Thus how the reading activity that took place in the past could be analysed and measured? And what methods could be used in case of extraordinary reading material, such as inscriptions on tombstones? In this article the author aims to show the possibility of investigating and measuring the process of reading inscriptions on tombstones in the past by applying Paul Connerton’s social theory on memory. Connerton’s model was tested on tombstones from Catholic cemeteries in Vilnius from the 19th century, the theoretical approach of applying this model is described in this article.
Keywords: epitaph, epigraphy, measuring the process of reading, history of communication